EFEKTIVITAS MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK KELAS 4 SDN BUGANGAN 01 - Binasiyah; Duwi Nuvitalia; Rizqi Para Anand; Aries Tika Damayan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to determine the effectiveness of Problem Based Learning on the mathematical literacy abilities of grade 4 students at SDN Bugangan 01. This type of research is experimental. The research design used was Pre-Experimental Design with a One-Group Pretest-Posttest Design model. The data collection methods used were tests and observations. The instrument used in this research was a test. The test used in this research is a formative test in the form of an essay. The test questions consist of 10 sample questions totaling 23 students. The results of this research show that students' mathematical literacy skills have increased based on the results of the descriptive test, with a higher post-test average score of 81.09 compared to the pre-test average score of 45.87. In addition, the average Ngain score of the respondents amounting to 65.5026%. This shows that the Ngain value is categorized as quite effective (range between 56% - 75%). Therefore, the problem based learning model is quite effective in improving students' mathematical literacy skills.